0.8–8 GHz 4-bit MMIC phase shifter for T/R modules. Issue 3 (21st May 2015) - Ferrari, Mauro; Piattella, Luca
Abstract : This paper presents the design approach and test results of a full passive, decade bandwidth GaAs MMIC, composed by a phase shifter (PS) with a cascaded absorptive s ingle pole double throw switch, suitable for transmitter/receiver modules in active electronically scanned array. The proposed PS – fabricated using a UMS GaAs 0.25 PHEMT process – combines all-pass filters with high-pass filters, in order to provide less than 13 dB insertion loss, less than ±20° phase error and less than ±2.5 dB amplitude error in the 0.8–8 GHz bandwidth.